2010
DOI: 10.1007/s00267-010-9460-z
|View full text |Cite
|
Sign up to set email alerts
|

Marine Conservation and Accession: The Future for the Croatian Adriatic

Abstract: The European Union (EU) is the world's largest trading bloc and the most influential supra-national organisation in the region. The EU has been the goal for many eastern European States, for Croatia accession remains a priority and underpins many of its national policies. However, entry into the EU requires certain commitments and concessions. In October 2003 the Croatian parliament declared an ecological and fisheries protection zone in the Adriatic. Under pressure the zone was suspended, finally entering int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…These principles were not applied by Croatia, indeed effort increased from 1997 to 2003, while it is now stationary. As raised during the integration process, and successively remarked by [54], the previous Croatian policy of State subsidies for fleet modernization was directly opposed to the Common Fisheries Policy (CFP) and the scientific advice of the GFCM, as its implementation could lead to an increase of fishing capacity [55]. The latest accession conferences [56] have now confirmed that Croatia has stopped its fleet modernization programme.…”
Section: Past Interactions Outcomes and Feedbacksmentioning
confidence: 92%
“…These principles were not applied by Croatia, indeed effort increased from 1997 to 2003, while it is now stationary. As raised during the integration process, and successively remarked by [54], the previous Croatian policy of State subsidies for fleet modernization was directly opposed to the Common Fisheries Policy (CFP) and the scientific advice of the GFCM, as its implementation could lead to an increase of fishing capacity [55]. The latest accession conferences [56] have now confirmed that Croatia has stopped its fleet modernization programme.…”
Section: Past Interactions Outcomes and Feedbacksmentioning
confidence: 92%
“…This membership has produced new opportunities to start negotiations for the establishment of an Adriatic transboundary LMPA between the two main Adriatic countries (Italy and Croatia) that could co-manage the area. The former European Commission's President Jose' Manuel Barroso has declared that the EU is willing to consider a special protection zone in the middle of the Adriatic [143], thereby demonstrating the Commission's intention to expand marine protection in this region. The EU is also currently funding a plethora of scientific projects on spatial planning within the Adriatic Sea [145][146][147][148][149], further highlighting the EU current effort to support spatial management aimed at promoting the recovery of Adriatic marine resources and economic sectors, and reduce conflicts among user groups.…”
Section: Political Opportunities and Legal Mechanisms For Establishinmentioning
confidence: 98%
“…In 2003, Croatia proposed the establishment of a 23,870 Km 2 Ecological and Fisheries Protection Zone (EFPZ) for marine biodiversity and fisheries conservation [143]. The EFPZ was approved by the Croatian government and enforced in January 2008.…”
Section: Political Opportunities and Legal Mechanisms For Establishinmentioning
confidence: 99%
“…2371 has not yet been applied by Croatia, and figures from the Croatian Bureau of Statistics (2009) show that fishing effort is continuously increasing. As noted by Mackelworth et al (2011), Croatian policy of State subsidies for fleet modernization is in direct opposition to the Common Fisheries Policy (CFP) and the scientific recommendations of the GFCM. Both Italy and Croatia have adopted technical measures such as minimum fish size (9 cm for anchovies in both jurisdictions, while the standard for sardines is 11 cm for the EU and 10 cm in Croatia), minimum mesh size (14 mm for EU purse seiners, 16 mm in Croatia; 20 mm for EU pelagic trawlers, 18 mm in Croatia), minimum distance from the coast for the pelagic trawlers (3 nm for the EU, 1 nm for Croatia) and temporary interruption of the activity (about 30 days in Italy in summer; about 30 days in Croatia in winter).…”
Section: Introductionmentioning
confidence: 96%